Liquid crystal alignment agent, polymer for obtaining the same, liquid crystal alignment film, and liquid crystal display element using the same

A polymer-based liquid crystal aligning agent with specific diamine and diisocyanate derivatives addresses reliability and solvent limitations, enabling high pretilt angle and voltage holding rate, suitable for large-screen, high-definition displays.

JP7610189B2Active Publication Date: 2025-01-08NISSAN CHEM CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023004168
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-23
Filing Date
2023-01-13
Publication Date
2025-01-08
Estimated Expiration
2039-03-20

AI Technical Summary

Technical Problem

Existing liquid crystal alignment films face challenges in achieving reliability, particularly with polyamic acid due to hydrolysis, and soluble polyimides face limitations in solvent choice leading to coating defects, which are exacerbated in large, high-definition LCD panels with diverse environments.

Method used

A liquid crystal aligning agent using a polymer composed of specific diamine and diisocyanate derivatives with a monomer containing a side chain, allowing for low-temperature firing and improved solubility, resulting in a high pretilt angle and high voltage holding rate.

Benefits of technology

The solution enables high-quality liquid crystal alignment films with excellent printability and reliability, suitable for large-screen, high-definition displays, by using a polymer that can be fired at low temperatures and maintains stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610189000001
    Figure 0007610189000001
  • Figure 0007610189000002
    Figure 0007610189000002
  • Figure 0007610189000003
    Figure 0007610189000003
Patent Text Reader

Abstract

The present invention provides a liquid crystal aligning agent that can be baked at a low temperature and has good printability, a polymer from which the liquid crystal aligning agent can be obtained, a liquid crystal alignment film that has good liquid crystal alignment properties and a high voltage holding ratio, and a liquid crystal display device having the liquid crystal alignment film. The liquid crystal aligning agent uses a polymer obtained from a diamine derivative represented by formula (1), a diisocyanate derivative, and a monomer selected from diamines or diisocyanates having a specific side chain. TIFF2023052403000046.tif24170 In the formula, A represents a divalent organic group selected from aliphatic hydrocarbon groups or aromatic hydrocarbon groups, and B and C each independently represent a single bond or an aliphatic hydrocarbon group having 1 to 5 carbon atoms. R1 represents an alkyl group having 1 to 4 carbon atoms, which may be branched. R2 represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 4 carbon atoms, or an organic group represented by formula (1-1). Ra and Rb each independently represent a hydrogen atom or an aliphatic hydrocarbon group having 1 to 2 carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal aligning agent, a polymer for obtaining the same, a liquid crystal alignment film, and a liquid crystal display device using the same. [Background technology]

[0002] In liquid crystal display elements, liquid crystal alignment films play a role in aligning liquid crystals in a certain direction. Currently, the main liquid crystal alignment films used industrially are formed by coating a substrate with a polyimide-based liquid crystal alignment agent made of polyamide acid (also called polyimide precursor or polyamic acid) or a polyimide solution, followed by baking.

[0003] Numerous techniques have been proposed to improve the display characteristics of liquid crystal display elements. For example, Patent Document 1 (JP Patent Publication No. 2-287324) proposes the use of a polyimide resin having a specific repeating structure to obtain a high voltage holding ratio (VHR). Also, Patent Document 2 (JP Patent Publication No. 10-104633) proposes the use of a soluble polyimide having a nitrogen atom in addition to an imide group to shorten the time it takes for an afterimage to be erased. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 2-287324 [Patent Document 2] Japanese Patent Application Publication No. 10-104633 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, with the increasing functionality and diversification of liquid crystal displays (LCD panels), development is progressing from displays using glass substrates to flexible displays using resin substrates (plastic substrates, i.e., film substrates). Accordingly, liquid crystal alignment films that can be obtained by firing at low temperatures are becoming necessary, and in addition, the reliability required of liquid crystal alignment films (high voltage holding ratio, etc.) is also becoming more and more important.

[0006] Materials used for liquid crystal alignment films include polyimide precursors such as polyamic acid and polyamic acid ester, and polyimides obtained by dehydrating them through baking or chemical reaction. Of these, polyamic acid is easy to synthesize and has excellent solubility in solvents, so it is possible to obtain a liquid crystal alignment agent that has excellent applicability to substrates and film formation properties. However, polyamic acid is easily decomposed by hydrolysis due to its structure, so it is difficult to ensure long-term reliability of liquid crystal alignment films obtained using it.

[0007] On the other hand, soluble polyimides (polyimides soluble in solvents obtained by the dehydration reaction of polyamic acid) are pre-imidized, so there is no need for a heat curing process to heat them to imidize them, and therefore they can be baked at a relatively low temperature. In addition, because they have excellent chemical stability and heat resistance, liquid crystal alignment films obtained using soluble polyimides tend to ensure long-term reliability. However, soluble polyimides have few options for solvents in which they can be dissolved, and therefore the solvents that can be used are limited. As a result, when soluble polyimides are used, precipitation occurs during application and film formation, and the coating film is prone to defects. In recent years, with the increase in size and resolution of LCD panels and the diversification of usage environments, there is a demand for methods that can solve each problem and improve various characteristics.

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a liquid crystal aligning agent which can be baked at a low temperature and has good printability (solubility of the resulting polymer in an organic solvent). Another object of the present invention is to provide a polymer from which the liquid crystal aligning agent can be obtained. Another object of the present invention is to provide a liquid crystal alignment film which has good liquid crystal alignment properties (i.e., can realize a high pretilt angle) and a high voltage retention rate. A further object of the present invention is to provide a liquid crystal display element having the liquid crystal alignment film. [Means for solving the problem]

[0009] As a result of intensive research, the present inventors have found that a polymer having a specific structure and a liquid crystal aligning agent using the same are effective for achieving the above object, and have completed the present invention. Note that the above polymer is novel, and the monomer for obtaining the above polymer also contains a novel compound.

[0010] That is, the present invention is summarized as follows: 1. to 10. 1. A liquid crystal aligning agent using a polymer obtained from a diamine derivative represented by the following formula (1), a diisocyanate derivative, and a monomer selected from diamines or diisocyanates having a specific side chain.

[0011] [ka] In the formula, D represents a single bond or a hydrocarbon group having 1 to 5 carbon atoms. 1 represents an alkyl group having 1 to 4 carbon atoms, which may be branched.

[0012] 2. The liquid crystal aligning agent according to 1., wherein the monomer containing the specific side chain is represented by the following formula (2):

[0013] [ka] In the formula, N represents an amino group or an isocyanate group, and R 3 teeth -O-, -COO-, or -CH 2 O- , X 1 , X 2, and X 3 each independently represents a benzene ring or a cyclohexane ring; p, q, and r each independently represent an integer of 0 or 1; R 4 is hydrogen atom, carbon number 1 or a steroid skeleton having 12 to 25 carbon atoms. Organic group Show If p=q=r=0, then R 4 is a linear alkyl group having 10 to 22 carbon atoms, or an organic group having a steroid skeleton and having 12 to 25 carbon atoms.

[0014] 3. The liquid crystal aligning agent according to 2., wherein the diisocyanate derivative has at least one of the structures represented by the following formulae (4-1) to (4-13).

[0015] [ka] In the formula, R 5 and R 6 each independently represents an aliphatic hydrocarbon group having 1 to 10 carbon atoms.

[0016] 4. A liquid crystal alignment film obtained from the liquid crystal aligning agent according to any one of 1. to 3.

[0017] 5. A liquid crystal display device using the liquid crystal alignment film described in 4.

[0018] 6. A polymer obtained from a diamino compound represented by the following formula (3-1), a diisocyanate derivative, and a monomer selected from diamines and diisocyanates having a specific side chain:

[0019] [ka] In the formula, R 1 represents an alkyl group having 1 to 4 carbon atoms, which may be branched. B represents a single bond or an aliphatic hydrocarbon group having 1 to 5 carbon atoms. Ra and Rb each independently represent a hydrogen atom or an aliphatic hydrocarbon group having 1 to 2 carbon atoms.

[0020] 7. The monomer containing the specific side chain is represented by the following formula (2): 6. The polymer according to claim 1.

[0021] [ka] In the formula, N represents an amino group or an isocyanate group, and R 3 teeth -O-, -COO-, or -CH 2 O- , X 1 , X 2 , and X 3 each independently represents a benzene ring or a cyclohexane ring; p, q, and r each independently represent an integer of 0 or 1; R 4 is a hydrogen atom, an alkyl group having 1 to 22 carbon atoms, or a steroid skeleton having 12 to 25 carbon atoms. Organic group Shows. However, R 3 is a single bond, p=q=r=0, and R 4 Excluding those where is a hydrogen atom.

[0022] 8. The diisocyanate derivative has at least one structure represented by the following formulas (4-1) to (4-13): 7. The polymer according to claim 1.

[0023] [ka] In the formula, R 5 and R 6 each independently represents an aliphatic hydrocarbon group having 1 to 10 carbon atoms.

[0024] 9. 6.~8. A liquid crystal aligning agent comprising the polymer according to any one of the above items.

[0025] 10. 9. A liquid crystal alignment film obtained from the liquid crystal alignment agent described above.

[0026] 11. 10. A liquid crystal display element using the liquid crystal alignment film according to claim 1. Effect of the Invention

[0027] According to the present invention, a liquid crystal alignment agent can be provided which can be baked at a low temperature, can produce a high-quality liquid crystal alignment film, and has excellent printability. Furthermore, according to the present invention, a novel polymer can be provided for obtaining the liquid crystal alignment agent. Furthermore, according to the present invention, a liquid crystal alignment film can be provided which can realize a high pretilt angle and has a high voltage holding ratio. Furthermore, according to the present invention, a liquid crystal display element using the liquid crystal alignment film can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The liquid crystal alignment agent according to one embodiment of the present invention contains a polymer according to one embodiment of the present invention, which is obtained from a diamine derivative (hereinafter sometimes referred to as "diamine") represented by formula (1), a diisocyanate derivative (hereinafter sometimes referred to as "diisocyanate"), and a monomer having a specific side chain and selected from diamines or diisocyanates (hereinafter sometimes referred to as "side chain-containing monomer").

[0029] <Diamine used in the present invention> The diamine used in the present invention is represented by the formula (1).

[0030] [ka] In the formula, A represents a divalent organic group such as an aliphatic hydrocarbon group or an aromatic hydrocarbon group, and B and C each independently represent a single bond or an aliphatic hydrocarbon group having 1 to 5 carbon atoms. R1 represents an alkyl group having 1 to 4 carbon atoms, which may be branched. R2 represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 4 carbon atoms, or an organic group represented by formula (1-1). Ra and Rb each independently represent a hydrogen atom or an aliphatic hydrocarbon group having 1 to 2 carbon atoms.

[0031] From the viewpoints of obtaining a liquid crystal alignment film excellent in polymerization reactivity of the monomer, heat resistance, and liquid crystal alignment property, etc., it is preferable that in formula (1), A is an aromatic hydrocarbon group, B is an aliphatic hydrocarbon group having 1 to 3 carbon atoms, and C is a single bond. Specific examples of formula (1) include the following structures.

[0032] [ka] In the formula, Ar is Arylene Group and D represents a single bond or a hydrocarbon group having 1 to 5 carbon atoms. 1 , R 2 , Ra and Rb are the above R 1 , R 2 , Ra and Rb.

[0033] In view of the fact that a reagent for synthesizing a diamine is easily available, that the reactivity with a diisocyanate is good, and that the physical properties of the resulting polymer are good, Ar in formula (3) is Phenylene group is preferred, R 2 is preferably a hydrogen atom. Therefore, formula (3) is preferably a structure represented by the following formula (3-a)'. In particular, in formula (3), Ra and Rb are preferably each a hydrogen atom. Therefore, formula (3) is particularly preferably represented by formula (3-a).

[0034] [ka] In the formula, D and R 1 are the above D and R 1 is synonymous with.

[0035] From the viewpoints of suitably obtaining the target monomer and easily achieving all of the above-mentioned properties, the above formula (3-a)' is preferably represented by the following formula (3-1).

[0036] [ka] In the formula, B, R 1 , Ra and Rb are the above B, R 1 In formula (3-1), when B has 1 or 2 carbon atoms and Ra and Rb are each a hydrogen atom, formula (3-1) is represented by formula (3-1a) or formula (3-1b).

[0037] [ka] In the formula, R 1 is the above R 1 is synonymous with.

[0038] However, specific examples of the diamine represented by formula (1) are not limited to the diamine represented by formula (3). In synthesizing the polymer, a part of the diamine represented by formula (1) or formula (3) may be replaced with the diamine represented by formula (5) described below, as long as the effects of the present invention (e.g., the ability to realize a high pretilt angle) are not impaired.

[0039] <Diisocyanate used in the present invention> The diisocyanate used in the present invention is represented by the following formula (4).

[0040] [ka] In the formula, X represents a divalent organic group. Formula (4) is preferably represented by formulae (4-1) to (4-13).

[0041] [ka] In the formula, R 5 and R 6 each independently represents an aliphatic hydrocarbon group having 1 to 10 carbon atoms.

[0042] When the aliphatic diisocyanates represented by formulae (4-1) to (4-5) are used, the resulting polymer dissolves better in a solvent than when the aromatic diisocyanates represented by formulae (4-6) to (4-13) are used. Meanwhile, the aromatic diisocyanates react better with diamines than the aliphatic diisocyanates. For example, aromatic diisocyanates such as those represented by formulae (4-6) and (4-7) react well with diamines, and can improve the heat resistance of the resulting liquid crystal alignment film.

[0043] From the viewpoints of being a versatile compound for obtaining the above polymer, and of obtaining good properties of the above polymer, etc., formula (4) is preferably formula (4-1), formula (4-7), formula (4-8), formula (4-9), or formula (4-10). From the viewpoints of obtaining good electrical properties of the liquid crystal alignment film, formula (5) is preferably formula (4-12), and from the viewpoints of obtaining good liquid crystal alignment property of the liquid crystal alignment film, formula (4-13) is preferred.

[0044] However, within the scope of the present invention, formula (4) is not limited to the above. Depending on the target properties of the resulting polymer, liquid crystal alignment agent, liquid crystal alignment film, etc., a diisocyanate that is easily available can be suitably used. Two or more diisocyanates may be used in combination.

[0045] <Side Chain-Containing Monomers Used in the Present Invention> The side chain-containing monomer used in the present invention is represented by formula (2).

[0046] [ka] In the formula, N represents an amino group or an isocyanate group, and R 3 represents a single bond or a divalent organic group, and X 1 , X 2 , and X 3 each independently represents a benzene ring or a cyclohexane ring; p, q, and r each independently represent an integer of 0 or 1; R 4represents a hydrogen atom, or a divalent organic group selected from an alkyl group having 1 to 22 carbon atoms or a divalent organic group having a steroid skeleton and having 12 to 25 carbon atoms.

[0047] The side chain-containing monomer represented by formula (2) contributes to increasing the pretilt angle of the liquid crystal. When the side chain-containing monomer is a diamine, the diamine preferably has a long chain alkyl group, a perfluoroalkyl group, an aromatic cyclic group, an aliphatic cyclic group, a substituent combining these, a steroid skeleton group, or the like. Since the preferred magnitude of the pretilt angle varies depending on the display mode of the liquid crystal display, the desired pretilt angle can be obtained by selecting the structure and the amount of the side chain-containing monomer introduced.

[0048] In the TN mode, which requires a pretilt angle of 3° to 5°, which is lower than that of the VA mode described below, and the OCB mode, which requires a pretilt angle of 8° to 20°, it is preferable to use a side chain-containing monomer having a relatively small function of increasing the pretilt angle (tilt expression ability). 3 is preferably -O- or -NHCO- (or -CONH-), p is preferably 0 to 1, q is preferably 0 to 1, and r is preferably 0. When p and / or q are 1, R 4 is preferably a linear alkyl group having 1 to 12 carbon atoms, and when p=q=r=0, R 4 is preferably a divalent organic group that is a linear alkyl group having 10 to 22 carbon atoms or an organic group having 12 to 25 carbon atoms and a steroid skeleton. Specific structures of side chain-containing monomers with low tilt expression ability are shown in Table 1, but formula (2) is not limited to the structures in Table 1. In each of [2-16] to [2-30] in Table 1, R 1 "-NHCO-" can be read as "-CONH-".

[0049] [Table 1]

[0050] From the viewpoint of improving the electrical properties of the resulting liquid crystal alignment film, preferred are side chain-containing monomers having long alkyl side chains such as those represented by [2-1] to [2-3] in Table 1. Also, from the viewpoint of improving the liquid crystal alignment properties and pretilt stability of the resulting liquid crystal alignment film, preferred are side chain-containing monomers represented by those represented by [2-25] to [2-27] in Table 1.

[0051] On the other hand, by using a side chain-containing monomer with a large tilt expression ability, the liquid crystal is easily aligned vertically. Therefore, the structure of formula (2) in the VA mode is, for example, R 3 is -O-, -COO-, or -CH 2 O- is preferable, p is preferably 0 to 1, q is preferably 0 to 1, and r is preferably 0 to 1; R 4 Preferably, p=q=r=0, R 4 is preferably a divalent organic group that is a linear alkyl group having 18 to 22 carbon atoms, or an organic group having a steroid skeleton and 12 to 25 carbon atoms. Specific structures of side chain-containing monomers having high tilt expression ability are shown in Tables 2-1 and 2-2, but formula (4) is not limited to the structures in Tables 2-1 and 2-2.

[0052] [Table 2-1]

[0053] [Table 2-2]

[0054] The side chain-containing monomers in Tables 2-1 and 2-2 have a high tilt expression ability, and are therefore preferred for use in VA mode. In particular, [2-43], [2-92], and the like have a high tilt expression ability, and are therefore easy to align liquid crystals vertically even with a relatively small amount of side chains. In particular, [2-52] and [2-101] have an extremely high tilt expression ability, and are able to align liquid crystals vertically even with a very small amount of side chains. Therefore, these side chain-containing monomers are preferred in terms of improving the printability of the liquid crystal alignment agent.

[0055] On the other hand, the side chain-containing monomer represented by formula (2) is selected from diamines or diisocyanates. However, diisocyanates are derived by reacting highly toxic phosgene or the like with diamines. Therefore, from the viewpoint of easy availability of side chain-containing monomers, it is more convenient to use diamines as the side chain-containing monomers. Therefore, N in formula (2) is preferably an amino group.

[0056] Monomers overlapping in Table 1, Table 2-1, and Table 2-2 may be used in either the TN mode, OCB mode, or the VA mode. In obtaining the above polymer, the content of the side chain-containing monomer is arbitrary within the scope of the present invention. For example, the molar number of the side chain-containing monomer relative to the total molar number of the diamine represented by formula (1) and the side chain-containing monomer may be 0.05 to 0.5.

[0057] <Diamine> In obtaining the above polymer, a part of the diamine represented by formula (1) may be replaced with other diamines (i.e., diamines that do not fall under the diamine represented by formula (1) and do not fall under the side chain-containing monomer). In general, there are many kinds of diamines, and many of them have organic groups with various functions. Therefore, by using other diamines in combination, it may be possible to impart further effects to the above polymer or to further improve the above effects of the diamine. The ratio of the number of moles of the other diamines to the number of moles of the diamine represented by formula (1) is arbitrary within a range in which the effects of the present invention (for example, the ability to realize a high pretilt angle) are not impaired. Of course, it is not necessary to use other diamines in combination. Examples of such other diamines include diamines represented by the following formula (5).

[0058] [ka] In the formula, Y represents a divalent organic group. Specific examples of the structure of Y are listed as the following formulae (Y-1) to (Y-147), but are not limited thereto. In the formulae (Y-1) to (Y-147), the black dots represent the bonding sites to the nitrogen atoms. R 7 each independently represents a hydrogen atom, a methyl group, or an ethyl group. The reaction of a tetracarboxylic dianhydride with a diamine gives a polyamic acid, and the reaction of a diisocyanate with a diamine gives a polyurea.

[0059] [ka]

[0060] [ka]

[0061] [ka]

[0062] [ka] In formulas (Y-108) to (Y-112), A 1 represents an alkyl group or a fluorine-containing alkyl group having 2 to 24 carbon atoms.

[0063] [ka] In formula (Y-113) to formula (Y-114), A 2 -O-, -OCH 2 -, -CH 2 O-, -COOCH 2 - or -CH 2 OCO- indicates A 3 represents an alkyl group, an alkoxy group, a fluorine-containing alkyl group, or a fluorine-containing alkoxy group having 1 to 22 carbon atoms.

[0064] [ka] In formulas (Y-115) to (Y-117), A 4 -COO-, -OCO-, -CONH-, -NHCO-, -COOCH 2 -, -CH 2 OCO-, -CH 2 O-, -OCH 2 - or -CH 2 - indicates A 5 represents an alkyl group, an alkoxy group, a fluorine-containing alkyl group, or a fluorine-containing alkoxy group having 1 to 22 carbon atoms.

[0065] [ka] In formula (Y-118) to formula (Y-119), A 6 -COO-, -OCO-, -CONH-, -NHCO-, -COOCH 2 -, -CH 2 OCO-, -CH 2 O-, -OCH 2 -, -CH 2 -, -O-, or -NH-; A 7 represents a fluorine group, a cyano group, a trifluoromethane group, a nitro group, an azo group, a formyl group, an acetyl group, an acetoxy group, or a hydroxyl group.

[0066] [ka] In formula (Y-120) to formula (Y-121), A 8 represents an alkyl group having 3 to 12 carbon atoms, and the cis-trans isomers of 1,4-cyclohexylene are both trans isomers.

[0067] [ka] In formula (Y-122) to formula (Y-123), A 9 represents an alkyl group having 3 to 12 carbon atoms, and the cis-trans isomers of 1,4-cyclohexylene are both trans isomers.

[0068] [ka] In formulas (Y-132) to (Y-137), A 12 -COO-, -OCO-, -CONH-, -NHCO-, -CH 2 -, -O-, -CO-, or -NH-; A 13 represents an alkyl group or a fluorine-containing alkyl group having 1 to 22 carbon atoms.

[0069] [ka] In the formulae (Y-140), (Y-144) and (Y-145), n represents an integer of 1 to 10.

[0070] <Polymer> The above polymers (polyurea and polyurea copolymers) are represented by formula (6).

[0071] [ka] In the formula, X represents a divalent organic group derived from a diisocyanate, and Y represents a divalent organic group derived from a diamine. 1 R represents an alkyl group having 1 to 4 carbon atoms, which may be branched. 2 represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 4 carbon atoms, or an organic group represented by the following formula (1-1): Ra and Rb each independently represent a hydrogen atom, or an aliphatic hydrocarbon group having 1 to 2 carbon atoms.

[0072] [ka] In the formula, the black dot represents the bond to the nitrogen atom, and R 1 , Ra and Rb are the above R 1 , Ra and Rb.

[0073] Polyurea forms strong hydrogen bonds due to the polarity of the urea bond site, so the resulting film has excellent mechanical strength. On the other hand, the strong hydrogen bond force can cause polymer aggregation and can worsen the stability of the polymer solution (the viscosity of the polymer solution increases, part of the polymer precipitates, the polymer solution gels, etc.). Therefore, depending on the structure of the polyurea, usable solvents are limited, and it is necessary to use, for example, a solvent with high polarity and high boiling point.

[0074] The polymer has a structure represented by formula (6), that is, a structure in which an organic group represented by formula (1-1) is substituted on the N atom of polyurea. The organic group represented by formula (1-1) inhibits the formation of hydrogen bonds, thereby preventing the aggregation of polymers. This greatly improves the stability of the polymer solution. Therefore, when obtaining a polyurea polymer solution, the range of solvents that can be used can be expanded, which in turn enables baking at low temperatures and greatly improves printability. Note that the urea bond site may form a hydantoin ring or an intermolecular crosslink, depending on the baking temperature during film formation.

[0075] <Reaction solution> The reaction solution (organic solvent used in the reaction to obtain the polymer) is not particularly limited as long as it is a solution in which the polymer can be dissolved. Specific examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methylcaprolactam, dimethyl sulfoxide, tetramethylurea, pyridine, dimethyl sulfone, hexamethyl sulfoxide, γ-butyrolactone, isopropyl alcohol, methoxymethylpentanol, dipentene, ethyl amyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isoamyl ketone, methyl isopropyl ketone, methyl cellosolve, ethyl cellosolve, methyl cellosolve acetate, ethyl cellosolve acetate, butyl carbitol, ethyl carbitol, ethylene glycol, ethylene glycol monoacetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, propylene glycol, propylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol-tert-butyl ether, dipropylene glycol monomethyl ether, diethylene glycol, diethylene Glycol monoacetate, diethylene glycol dimethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monoacetate monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methylcyclohexene, propyl ether, dihexyl ether, dioxane, n-hexane, n-pentane, n-octane, diethyl ether, cyclohexanone, ethylene carbonate, propylene carbonate, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate,Examples of the solvent include ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, diglyme, 4-hydroxy-4-methyl-2-pentanone, 3-methoxy-N,N-dimethylpropanamide, 3-ethoxy-N,N-dimethylpropanamide, and 3-butoxy-N,N-dimethylpropanamide. These may be used alone or in combination of two or more. As long as the polymer does not precipitate, even a solution that does not dissolve the polymer may be mixed with the reaction solution and used.

[0076] In addition, since moisture in the reaction solution inhibits the polymerization reaction and further causes hydrolysis of the produced polymer, it is preferable to use a reaction solution that has been dehydrated and dried. When reacting a diisocyanate with a diamine in a reaction solution, the reaction solution in which the diamine is dispersed or dissolved is stirred, and the diisocyanate is added as is or after being dispersed or dissolved in the reaction solution, a method in which the diamine is added to the reaction solution in which the diisocyanate is dispersed or dissolved, or a method in which the diisocyanate and the diamine are added alternately to the reaction solution may be used, and any of these methods may be used.

[0077] In addition, when the diisocyanate or diamine is composed of a plurality of compounds, they may be reacted in a premixed state, or may be reacted individually in sequence, or low molecular weight compounds that have been reacted individually may be mixed and reacted to form a high molecular weight compound. The polymerization temperature at this time can be selected from -20°C to 150°C, but is preferably in the range of -5°C to 100°C. In addition, the reaction can be carried out at any concentration, but if the concentration is too low, it is difficult to obtain a high molecular weight polymer, and if the concentration is too high, the viscosity of the reaction solution becomes too high, making it difficult to stir uniformly. Therefore, the total concentration of the diisocyanate (diisocyanate represented by formula (4)) and the diamine (diisocyanate represented by formulas (1) and (5)) in the reaction solution is preferably 1% by mass to 50% by mass, more preferably 5% by mass to 30% by mass. The reaction can be carried out at a high concentration in the early stages, and then the reaction solution can be added.

[0078] In the polymerization reaction of polyurea, the ratio of the total number of moles of diisocyanate (diisocyanate represented by formula (4)) to the total number of moles of diamine (diamine represented by formula (1) and formula (5)) is preferably 0.8 to 1.2. As in the case of a normal polycondensation reaction, the closer this molar ratio is to 1.0, the higher the molecular weight of the polymer produced.

[0079] [Polymer recovery] To recover the polymer produced from the reaction solution, the reaction solution may be poured into a poor solvent to precipitate the polymer. Examples of poor solvents include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, benzene, and water. The polymer precipitated by pouring into a poor solvent can be recovered by filtration, and then dried at room temperature or by heating under normal or reduced pressure. In addition, the recovered polymer can be redissolved in an organic solvent, and the reprecipitation and re-recovery operations can be repeated two to ten times to reduce impurities in the polymer. Examples of poor solvents in this case include alcohols, ketones, and hydrocarbons. It is preferable to use three or more poor solvents selected from these because the efficiency of purification is further improved.

[0080] The molecular weight of the polymer is preferably 5,000 to 1,000,000, more preferably 10,000 to 150,000, in terms of weight average molecular weight measured by GPC (Gel Permeation Chromatography), taking into consideration the strength of the coating film obtained from the polymer, the ease of work in forming the coating film, the uniformity of the coating film thickness, and the like.

[0081] <Liquid crystal alignment agent> The liquid crystal alignment agent according to one embodiment of the present invention is a coating liquid for forming a liquid crystal alignment film, in which a resin component for forming a coating film (resin film) is dissolved in an organic solvent. The resin component contains at least one of the above polymers. The content of the resin component in the liquid crystal alignment agent is preferably 2% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, and particularly preferably 3% by mass to 10% by mass. In the present invention, the polymers contained in the resin component may all be the above polymers (polyurea and polyurea copolymer), and may contain other polymers (other polymers) within the scope of the present invention. The content of the other polymers in the resin component is 0.5% by mass to 15% by mass, preferably 1% by mass to 10% by mass. Examples of such other polymers include acrylic polymers, methacrylic polymers, novolac resins, polyhydroxystyrene, polyimide precursors, polyimides, polyamides, polyesters, cellulose, polysiloxanes, and the like.

[0082] The organic solvent used in the liquid crystal alignment agent is not particularly limited as long as it is an organic solvent that dissolves the resin component.Specific examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-methylcaprolactam, 2-pyrrolidone, N-ethylpyrrolidone, N-vinylpyrrolidone, dimethylsulfoxide, tetramethylurea, pyridine, dimethylsulfone, hexamethylsulfoxide, γ-butyrolactone, 3-methoxy-N,N-dimethylpropanamide, 3-ethoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, 1,3-dimethyl-imidazolidinone, ethyl amyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isoamyl ketone, methyl isopropyl ketone, cyclohexanone, ethylene carbonate, propylene carbonate, diglyme, and 4-hydroxy-4-methyl-2-pentanone. These may be used alone or in combination of two or more.

[0083] The liquid crystal alignment agent may contain components other than those described above, such as a solvent or compound that improves the uniformity of the film thickness or the surface smoothness of the coating film formed by applying the liquid crystal alignment agent, or a compound that improves the adhesion between the liquid crystal alignment film and the substrate.

[0084] Examples of solvents (poor solvents) that improve the uniformity of the film thickness and the smoothness of the surface include solvents having low surface tension, such as isopropyl alcohol, methoxymethyl pentanol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, methyl cellosolve acetate, ethyl cellosolve acetate, butyl carbitol, ethyl carbitol, ethyl carbitol acetate, ethylene glycol, ethylene glycol monoacetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, propylene glycol, propylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol-tert-butyl ether, dipropylene glycol monomethyl ether, diethylene glycol, diethylene glycol monoacetate, diethylene glycol dimethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monoacetate monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol Licorice monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methylcyclohexene, propyl ether, dihexyl ether, 1-hexanol, n-hexane, n-pentane, n-octane, diethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate , propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-butoxy-2-propanol, 1-phenoxy-2-propanol, propylene glycol monoacetate, propylene glycol diacetate,Examples of the poor solvent include propylene glycol-1-monomethyl ether-2-acetate, propylene glycol-1-monoethyl ether-2-acetate, dipropylene glycol, 2-(2-ethoxypropoxy)propanol, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, and isoamyl lactate. These poor solvents may be used alone or in combination. When the poor solvent is used, it is preferably 5% to 80% by mass, more preferably 20% to 60% by mass of the total organic solvent contained in the liquid crystal alignment agent.

[0085] Compounds that improve the uniformity of the film thickness and the smoothness of the coating surface include fluorine-based surfactants, silicone-based surfactants, nonionic surfactants, etc. More specifically, for example, EFTOP EF301, EF303, EF352 (manufactured by Tochem Products), Megafac F171, F173, R-30 (manufactured by Dainippon Ink Co., Ltd.), Fluorad FC430, FC431 (manufactured by Sumitomo 3M), Asahiguard AG710, Surflon S-382, SC101, SC102, SC103, SC104, SC105, SC106 (manufactured by Asahi Glass Co., Ltd.), etc. The proportion of these surfactants used is preferably 0.01 to 2 parts by mass, more preferably 0.01 to 1 part by mass, relative to 100 parts by mass of the resin component contained in the liquid crystal alignment agent.

[0086] Specific examples of compounds that improve the adhesion between the liquid crystal alignment film and the substrate include the following functional silane-containing compounds and epoxy group-containing compounds. For example, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 2-aminopropyltrimethoxysilane, 2-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltriethoxy ... -Aminopropyltriethoxysilane, N-triethoxysilylpropyltriethylenetriamine, N-trimethoxysilylpropyltriethylenetriamine, 10-trimethoxysilyl-1,4,7-triazadecane, 10-triethoxysilyl-1,4,7-triazadecane, 9-trimethoxysilyl-3,6-diazanonyl acetate, 9-triethoxysilyl-3,6-diazanonyl acetate, N-benzyl-3-aminopropyltrimethoxysilane, N-benzyl-3-aminopropyltriethoxy Silane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, N-bis(oxyethylene)-3-aminopropyltrimethoxysilane, N-bis(oxyethylene)-3-aminopropyltriethoxysilane, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether , neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerin diglycidyl ether, 2,2-dibromoneopentyl glycol diglycidyl ether, 1,3,5,6-tetraglycidyl-2,4-hexanediol, N,N,N',N',-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N',-tetraglycidyl-4,4'-diaminodiphenylmethane, and the like.

[0087] Furthermore, in order to improve the adhesion between the substrate and the film and to prevent deterioration of electrical properties caused by irradiation with light from a backlight, the following phenoplast additives may be added. Specific phenoplast additives are shown below, but are not limited to these structures.

[0088] [ka]

[0089] When a compound that improves the adhesion between the substrate and the film is used, the amount of the compound used is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, per 100 parts by mass of the resin component contained in the liquid crystal alignment agent. If the amount used is less than the above value, the adhesion is difficult to improve, and if the amount used is more than the above value, the liquid crystal alignment may deteriorate.

[0090] In addition to the above-mentioned solvents and compounds, the liquid crystal alignment agent may contain a dielectric or conductive substance for the purpose of changing the electrical properties such as the dielectric constant and conductivity of the liquid crystal alignment film, and further may contain a specific crosslinking compound for the purpose of increasing the hardness and density of the film when made into a liquid crystal alignment film, as long as the effects of the present invention are not impaired.

[0091] <Liquid crystal alignment film / Liquid crystal display element> The liquid crystal alignment agent is applied to a substrate and baked, and then an alignment treatment is performed if necessary. In applications such as vertical alignment, the liquid crystal alignment film according to one embodiment of the present invention can be obtained without the alignment treatment. As the substrate, a highly transparent glass substrate or a plastic substrate (e.g., an acrylic substrate or a polycarbonate substrate) can be used. In addition, it is preferable to use a substrate on which an ITO electrode or the like for driving the liquid crystal is formed, from the viewpoint of simplifying the process of manufacturing a liquid crystal display element. In addition, in a reflective liquid crystal display element, an opaque material such as a silicon wafer can be used as the substrate on one side, and in this case, the electrode can be made of a material that reflects light, such as aluminum. The method of applying the liquid crystal alignment agent is not particularly limited, but in industry, spin coat printing, screen printing, offset printing, flexographic printing, inkjet printing, and the like are generally used. Other application methods include dipping, roll coater, slit coater, spinner, and the like, and these methods may be used depending on the purpose.

[0092] The baking can be performed at 50°C to 300°C, preferably 80°C to 250°C, using a heating means such as a hot plate. The organic solvent in the liquid crystal alignment agent is evaporated to form a coating film. If the coating film is too thick, the power consumption of the liquid crystal display element is likely to increase, and if it is too thin, the reliability of the liquid crystal display element may decrease. Therefore, the thickness of the coating film is preferably 5 nm to 300 nm, more preferably 10 nm to 150 nm.

[0093] The above-mentioned method can be used to obtain a substrate with a liquid crystal alignment film from the liquid crystal alignment agent, and then a liquid crystal cell can be produced by a known method to obtain a liquid crystal display element according to one embodiment of the present invention. One example of a method for producing a liquid crystal cell is to prepare a pair of substrates on which a liquid crystal alignment film is formed, to spray spacers on the liquid crystal alignment film of one substrate, to bond the other substrate with the liquid crystal alignment film surface facing inward, to inject liquid crystal under reduced pressure, and to seal the substrate. Alternatively, a method can be used in which liquid crystal is dropped onto the liquid crystal alignment film surface on which the spacers have been sprayed, and then the substrates are bonded together to seal the substrate. The thickness of the spacer in this case is preferably 1 μm to 30 μm, more preferably 2 μm to 10 μm. The liquid crystal display element produced using the liquid crystal alignment agent is highly reliable, and can therefore be suitably used in large-screen, high-definition liquid crystal televisions and the like. EXAMPLES

[0094] <Synthesis of diamine> Example 1 Synthesis of ethyl(4-aminobenzyl)glycinate [NG4ABA]

[0095] [ka]

[0096] 1st process In a 1L four-neck flask equipped with a nitrogen inlet tube and a reflux tube, 105.6g (0.694mol) of glycine ethyl hydrochloride, 300g of THF, and 93.6g (0.925mol) of triethylamine were added, and the mixture was stirred at room temperature for 1 hour using a mechanical stirrer, then heated to a temperature at which THF refluxes (set at 70°C), and 50.0g (0.231mol) of 4-nitrobenzyl bromide was dissolved in 500.0g of THF and slowly dropped into the mixture. After the dropwise addition was completed, the reaction was continued for another 24 hours. The reaction was terminated when 4-nitrobenzyl bromide disappeared, and the precipitated solid was removed by filtration, and THF was removed by a rotary evaporator. The obtained crude product was redissolved in 300.0g of ethyl acetate. This solution was washed three times with 100g of pure water, 300g of 10% aqueous hydrochloric acid solution was added, stirred for one hour, the aqueous layer was collected, and the aqueous layer was washed three times with 100g of ethyl acetate. 300g of ethyl acetate was further added to the aqueous layer, potassium carbonate was slowly added, the pH was adjusted to about 10, and stirred for one hour, the organic phase was collected, and washed three times with 100g of pure water. Anhydrous magnesium sulfate was added to this organic phase to dry it, filtered, activated carbon was added and stirred for a while, the activated carbon was removed by filtration, and the solvent was removed with a rotary evaporator to obtain 46.0g (0.193mol) of a pale yellow viscous substance, which was the target product (nitro form). The target product was obtained, 1 This was confirmed by H-NMR. 1 H NMR (500MHz, CDCl 3 ):δ 8.2(2H), 7.53(2H), 4.22(2H), 3.93(2H), 3.42(2H), 1.89(1H), 1.27(3H)

[0097] 2nd process 45.0g (0.19mol) of the nitro compound obtained above, 300.0g of THF, and 4.5g of iron-doped platinum carbon were added to a 500ml four-neck flask equipped with a nitrogen inlet tube and a stirrer, and the atmosphere inside the vessel was carefully replaced with a hydrogen atmosphere and reacted at room temperature for 24 hours. The reaction was terminated when the raw materials disappeared, the platinum carbon was removed with a membrane filter, activated carbon (Shirasagi) was added to the filtrate, and the mixture was stirred at 40°C for 30 minutes. After that, it was filtered again, the solvent was removed with a rotary evaporator, and the mixture was dried with a high vacuum pump to obtain the target product, a pale yellow viscous product, 35.4g (0.17mol: yield 89%). The target product (NG4ABA) was obtained, 1 This was confirmed by H-NMR. 1 H NMR (500MHz, CDCl 3 ):δ 6.99(2H), 6.63(2H), 4.15(2H), 3.70(2H), 3.38(2H), 3.00(2H), 1.24(3H)

[0098] Example 2 Synthesis of ethyl(4-aminophenethyl)glycinate [NG4APhA]

[0099] [ka]

[0100] 1st process In a 1L four-neck flask equipped with a nitrogen inlet tube and a reflux tube, 50g (0.246mol) of 4-nitrophenethylamine hydrochloride, 500g of THF, and 62.1g (0.604mol) of triethylamine were added, and the mixture was stirred at room temperature for 1 hour using a mechanical stirrer, heated to a temperature at which THF refluxes (set at 70°C), and 25.1g (0.205mol) of 2-chloroethyl acetate was dissolved in 300g of THF and slowly dropped. After the dropwise addition was completed, the reaction was continued for another 24 hours. The reaction was terminated when 2-chloroethyl acetate disappeared (confirmed by HPLC), the precipitated solid was removed by filtration, THF was removed by a rotary evaporator, and the obtained crude product was redissolved in 500g of ethyl acetate. This solution was washed three times with 100g of pure water, 500g of 10% aqueous hydrochloric acid was added, and the mixture was stirred for one hour. The aqueous layer was collected, and the aqueous layer was washed three times with 100g of ethyl acetate. 500g of ethyl acetate was further added to the aqueous layer, potassium carbonate was slowly added, the pH was adjusted to about 10, and the mixture was stirred for 1 hour. The organic phase was then recovered and washed three times with 100g of pure water. Anhydrous magnesium sulfate was added to this organic phase, which was then dried, filtered, activated carbon was added, and the mixture was stirred for a while. The activated carbon was then removed by filtration, and the solvent was removed using a rotary evaporator to obtain 34.2g (0.136mol: yield 66%) of the desired pale yellow viscous product. The obtained product (nitro form) was confirmed by 1 This was confirmed by H-NMR. 1 H NMR (500MHz, CDCl 3 ):δ 8.14(2H), 7.37(2H), 4.16(2H), 3.43(2H), 2.95(4H), 2.19(1H), 1.25(3H)

[0101] 2nd process 30.0 g of the nitro compound obtained above, 300 g of THF, and 3.0 g of iron-doped platinum carbon were added to a 500 ml four-neck flask equipped with a nitrogen inlet tube and a stirrer, and the atmosphere inside the vessel was carefully replaced with a hydrogen atmosphere and allowed to react at room temperature for 24 hours. The reaction was terminated when the raw materials had disappeared, the platinum carbon was removed with a membrane filter, and activated carbon (Shirasagi) was added to the filtrate and stirred at 40°C for 30 minutes. It was then filtered again, the solvent was removed with a rotary evaporator, and the mixture was dried with a high vacuum pump to obtain 25.1 g (0.113 mol: 95% yield) of a pale yellow viscous material, the target product (NG4APhA). Confirming that the target product had been obtained, 1 This was confirmed by H-NMR. 1 H NMR (500MHz, CDCl 3 ):δ 6.99(2H), 6.60(2H), 4.18(2H), 3.42(2H), 2.89(2H), 2.86(2H), 2.75(2H), 1.24(3H)

[0102] <Abbreviations> The abbreviations used in the preparation of the liquid crystal alignment agent are as follows. (Diisocyanate) IDI: Isophorone diisocyanate DI-2MG: 1,2-bis(4-isocyanatophenoxy)ethane

[0103] [ka] (Diamine) p-PDA: paraphenylenediamine NG4ABA: Ethyl (4-aminobenzyl) glycinate NG4APhA: Ethyl (4-aminophenethyl) glycinate Me4APhA: N-methyl-4-aminophenethylamine DA-3MG: 1,3-di(4-aminophenoxy)propane APC16: 2-Hexadecyloxy-1,3-diaminobenzene PCH7: 4-(4-(4-heptylcyclohexyl)phenoxy)benzene-1,3-diamine

[0104] [ka]

[0105] (Tetracarboxylic acid dianhydride) CBDA: Cyclobutanetetracarboxylic dianhydride

[0106] (solvent) NMP: N-methyl-2-pyrrolidone BCS: Butyl cellosolve GBL: gamma-butyrolactone

[0107] The conditions for measuring the molecular weight of polyimide are as follows. Apparatus: Senshu Scientific Co., Ltd. room temperature gel permeation chromatography (GPC) apparatus (SSC-7200) Column: Shodex column (KD-803, KD-805) Column temperature: 50℃ Eluent: N,N'-dimethylformamide (with lithium bromide monohydrate (LiBr H 2 O) is 30mmol / L, phosphoric acid anhydrous crystal (o-phosphoric acid) is 30mmol / L, THF is 10ml / L) Flow rate: 1.0ml / min Standard samples for creating calibration curves: TSK standard polyethylene oxide (molecular weights: approximately 9,000,000, 150,000, 100,000, and 30,000) manufactured by Tosoh Corporation, and polyethylene glycol (molecular weights: approximately 12,000, 4,000, and 1,000) manufactured by Polymer Laboratory Co., Ltd.

[0108] <Polymer synthesis> Example 3 DI-2MG / NG4ABA, APC16 2.00g (6.75mmol) of DI-2MG was weighed out into a 50ml two-neck flask equipped with a nitrogen inlet tube and a stirrer, 19.61g of NMP was added to dissolve it, 0.24g (0.68mmol) of APC16 was added, and the mixture was reacted at room temperature for 1 hour. 1.22g (5.88mmol) of NG4ABA was further added, and the mixture was reacted at 40°C under a nitrogen atmosphere for 24 hours. As a result, a polymer (polymer solution: P-1) with a concentration of 15% by mass and a viscosity of 220mPas was obtained. The weight-average molecular weight of the obtained polymer was Mw: 37200.

[0109] Example 4 DI-2MG / NG4APhA, APC16 2.00g (6.75mmol) of DI-2MG was weighed out into a 50ml two-neck flask equipped with a nitrogen inlet tube and a stirrer, 20.12g of NMP was added to dissolve it, 0.24g (0.68mmol) of APC16 was added, and the mixture was reacted at room temperature for 1 hour. 1.31g (5.88mmol) of NG4APhA was further added, and the mixture was reacted at 40°C under a nitrogen atmosphere for 24 hours. As a result, a polymer (polymer solution: P-2) with a concentration of 15% by mass and a viscosity of 280mPas was obtained. The weight-average molecular weight of the obtained polymer was Mw: 39100.

[0110] Example 5 DI-2MG / NG4ABA, PCH7 2.00g (6.75mmol) of DI-2MG was weighed out into a 50ml two-neck flask equipped with a nitrogen inlet tube and a stirrer, 20.57g of NMP was added to dissolve it, 0.52g (1.36mmol) of PCH7 was added, and the mixture was reacted at room temperature for 1 hour. 1.11g (5.34mmol) of NG4ABA was further added, and the mixture was reacted at 40°C under a nitrogen atmosphere for 24 hours. As a result, a polymer (polymer solution: P-3) with a concentration of 15% by mass and a viscosity of 230mPas was obtained. The weight-average molecular weight of the obtained polymer was Mw: 40200.

[0111] Example 6 IDI, DI-2MG / NG4ABA, PCH7 In a 50 ml two-neck flask equipped with a nitrogen inlet tube and a stirrer, 1.00 g (3.38 mmol) of DI-2MG and 14.05 g of NMP were added and dissolved, and 0.37 g (0.97 mmol) of PCH7 was added, and the mixture was reacted at room temperature for 1 hour. Further, 0.32 g (1.45 mmol) of IDI and 0.79 g (3.81 mmol) of NG4ABA were added, and the mixture was reacted at 40° C. for 24 hours under a nitrogen atmosphere. As a result, a polymer (polymer solution: P-4) with a concentration of 15% by mass and a viscosity of 300 mPas was obtained. The weight-average molecular weight of the obtained polymer was Mw: 44,200.

[0112] Comparative Example 1 DI-2MG / Me4APhA, APC16 2.00g (6.75mmol) of DI-2MG was weighed out into a 50ml two-neck flask equipped with a nitrogen inlet tube and a stirrer, 17.73g of NMP was added to dissolve it, 0.24g (0.68mmol) of APC16 was added, and the mixture was reacted at room temperature for 1 hour. 0.89g (5.94mmol) of Me4APhA was further added, and the mixture was reacted at 40°C under a nitrogen atmosphere for 24 hours. As a result, a polymer (polymer solution: PRef-1) with a concentration of 15% by mass and a viscosity of 320mPas was obtained. The weight-average molecular weight of the obtained polymer was Mw: 39900.

[0113] Comparative Example 2 DI-2MG / Me4APhA, PCH7 2.00g (6.75mmol) of DI-2MG was weighed out into a 50ml two-neck flask equipped with a nitrogen inlet tube and a stirrer, 18.7g of NMP was added to dissolve it, 0.51g (1.35mmol) of PCH7 was added, and the mixture was reacted at room temperature for 1 hour. 0.79g (5.27mmol) of Me4APhA was further added, and the mixture was reacted at 40°C under a nitrogen atmosphere for 24 hours. As a result, a polymer (polymer solution: PRef-2) with a concentration of 15% by mass and a viscosity of 280mPas was obtained. The weight-average molecular weight of the obtained polymer was Mw: 37200.

[0114] Comparative Example 3 CBDA / p-PDA, PCH7 In a 50 ml two-neck flask equipped with a nitrogen inlet tube and a stirrer, 1.00 g (9.24 mmol) of p-PDA and 0.88 g (2.31 mmol) of PCH7 were weighed out and dissolved by adding 23.12 g of NMP. Then, 2.20 g (11.20 mmol) of CBDA was added and reacted for 24 hours at room temperature under a nitrogen atmosphere. As a result, a polymer (polymer solution: PRef-3) with a concentration of 15% by mass and a viscosity of 380 mPas was obtained. The weight-average molecular weight of the obtained polymer was Mw: 44,200.

[0115] <Adjustment of liquid crystal alignment agent> Example 7 10.0 g of the polymer (P-1) obtained in Example 3 was weighed into a 50 ml Erlenmeyer flask equipped with a stirrer, and 2.5 g of NMP, 5.0 g of GBL, and 7.5 g of BCS were added, followed by stirring at room temperature for 30 minutes. As a result, a liquid crystal alignment agent (AL-1) with a solid content of 6.0 mass%, NMP 44 mass%, GBL 20 mass%, and BCS 30 mass% was obtained.

[0116] Example 8 10.0 g of the polymer (P-2) obtained in Example 4 was weighed into a 50 ml Erlenmeyer flask equipped with a stirrer, and 2.5 g of NMP, 5.0 g of GBL, and 7.5 g of BCS were added, followed by stirring at room temperature for 30 minutes. As a result, a liquid crystal alignment agent (AL-2) with a solid content of 6.0 mass%, NMP 44 mass%, GBL 20 mass%, and BCS 30 mass% was obtained.

[0117] Example 9 10.0 g of the polymer (P-3) obtained in Example 5 was weighed into a 50 ml Erlenmeyer flask equipped with a stirrer, and 2.5 g of NMP, 5.0 g of GBL, and 7.5 g of BCS were added, followed by stirring at room temperature for 30 minutes. As a result, a liquid crystal alignment agent (AL-3) with a solid content of 6.0 mass%, NMP 44 mass%, GBL 20 mass%, and BCS 30 mass% was obtained.

[0118] Example 10 10.0 g of the polymer (P-4) obtained in Example 6 was weighed into a 50 ml Erlenmeyer flask equipped with a stirrer, and 2.5 g of NMP, 5.0 g of GBL, and 7.5 g of BCS were added, followed by stirring at room temperature for 30 minutes. As a result, a liquid crystal alignment agent (AL-4) with a solid content of 6.0 mass%, NMP 44 mass%, GBL 20 mass%, and BCS 30 mass% was obtained.

[0119] Comparative Example 4 10.0 g of the polymer (PRef-1) obtained in Comparative Example 1 was weighed into a 50 ml Erlenmeyer flask equipped with a stirrer, and 2.5 g of NMP, 5.0 g of GBL, and 7.5 g of BCS were added, followed by stirring at room temperature for 30 minutes. As a result, a liquid crystal alignment agent (AL-5) with a solid content of 6.0 mass%, NMP 44 mass%, GBL 20 mass%, and BCS 30 mass% was obtained.

[0120] Comparative Example 5 10.0 g of the polymer (PRef-2) obtained in Comparative Example 2 was weighed into a 50 ml Erlenmeyer flask equipped with a stirrer, and 2.5 g of NMP, 5.0 g of GBL, and 7.5 g of BCS were added, followed by stirring at room temperature for 30 minutes. As a result, a liquid crystal alignment agent (AL-6) with a solid content of 6.0 mass%, NMP 44 mass%, GBL 20 mass%, and BCS 30 mass% was obtained.

[0121] Comparative Example 6 10.0 g of the polymer (PRef-3) obtained in Comparative Example 3 was weighed into a 50 ml Erlenmeyer flask equipped with a stirrer, and 2.5 g of NMP, 5.0 g of GBL, and 7.5 g of BCS were added, followed by stirring at room temperature for 30 minutes. As a result, a liquid crystal alignment agent (AL-7) with a solid content of 6.0 mass%, NMP 44 mass%, GBL 20 mass%, and BCS 30 mass% was obtained.

[0122] The liquid crystal alignment agents of Examples 7 to 10 (AL-1 to AL-4) and the liquid crystal alignment agents of Comparative Examples 4 to 6 (AL-5 to AL-7) were used to evaluate liquid crystal alignment films based on the following method.

[0123] <Evaluation of whitening resistance and coatability (printability)> A drop of each of the obtained liquid crystal alignment agents was dropped onto a thoroughly washed Cr substrate, and the substrate was left at room temperature of 25°C and humidity of 60%, and the time until the substrate turned white (whitened) was measured. The whitening resistance was evaluated based on the measured time.

[0124] The liquid crystal alignment agent was filtered through a 1.0 μm filter, and then flexographically printed on a washed Cr plate using an alignment film printer ("Angstromer" manufactured by Nissha Printing Co., Ltd.) to perform a coatability test.

[0125] About 1.0 ml of liquid crystal alignment agent was dropped onto the anilox roll, and after 10 idle runs, the printer was stopped for 10 minutes to dry the printing plate. Then, printing was performed on one Cr substrate, and the printed substrate was left on a hot plate at 70°C for 5 minutes to pre-dry the coating film, and the film condition was observed. Film thickness unevenness and film thickness unevenness at edges were mainly observed visually and with an optical microscope (Nikon Corporation "ECLIPSE ME600") at a magnification of 50 times.

[0126] <Evaluation of Liquid Crystal Alignment, Voltage Holding Ratio, and Pretilt Angle> [Observation of liquid crystal alignment and preparation of liquid crystal cells] After filtering the liquid crystal alignment agent with a 1.0 μm filter, it was applied by spin-coating to a substrate with electrodes (a glass substrate with a size of 30 mm wide x 40 mm long and a thickness of 1.1 mm. The electrodes were rectangular with a width of 10 mm and a length of 40 mm, and were ITO electrodes with a thickness of 35 nm). After drying for 5 minutes on a hot plate at 50°C, it was baked for 20 minutes in an IR oven at 180°C to form a coating film with a thickness of 100 nm. This film was rubbed with a rayon cloth (YA-20R manufactured by Yoshikawa Kako) (roller diameter: 120 mm, roller rotation speed: 1000 rpm, moving speed: 20 mm / sec, indentation length: 0.4 mm), and then washed by irradiating ultrasonic waves in pure water for 1 minute, and water droplets were removed by air blowing, and then dried at 80°C for 15 minutes to obtain a substrate with a liquid crystal alignment film.

[0127] Two substrates with the above liquid crystal alignment film were prepared, and 4 μm spacers were sprayed on the liquid crystal alignment film surface of one of them, and then a sealant was printed on top of it. The other substrate was attached so that the rubbing direction was in the opposite direction and the film surface faced each other, and then the sealant was cured to prepare an empty cell. MLC-2041 (manufactured by Merck Ltd.) was injected into this empty cell by the reduced pressure injection method, and the injection port was sealed to obtain a liquid crystal cell. After that, the liquid crystal alignment was observed, and then the liquid crystal cell was heated at 110°C for 1 hour and left at 23°C overnight to obtain a liquid crystal cell for measuring the voltage holding ratio.

[0128] Using the liquid crystal cell for measuring the voltage holding ratio obtained by the above procedure, a voltage of 1V was applied for 60μs at a temperature of 60℃, the voltage was measured after 166.7ms, and the voltage holding ratio was calculated as the extent to which the voltage was held. The voltage holding ratio was measured using a VHR-1 voltage holding ratio measuring device manufactured by Toyo Corporation.

[0129] [Evaluation of pretilt angle] The pretilt angle was measured using an Axo Scan Mueller matrix polarimeter manufactured by Optometrics.

[0130] The results of the various evaluations mentioned above are shown in Table 3.

[0131] [Table 3]

[0132] The liquid crystal alignment agents of Examples 7 to 10 have superior whitening resistance and good printability compared to the comparative examples. Comparative Example 6 is a polyamic acid-based material, and therefore has good whitening resistance and printability. Examples 7 to 10 are expected to have whitening resistance and printability equivalent to or better than Comparative Example 5.

[0133] In addition, the liquid crystal cells obtained using the liquid crystal alignment agents of Examples 7 to 10 have a high pretilt angle and a high voltage retention rate. For example, the side chain-containing monomer used in this example contributes to increasing the pretilt angle of the liquid crystal, so it is expected that the desired pretilt angle can be obtained by variously selecting the structure and amount of the side chain-containing monomer. The liquid crystal alignment film, which is one aspect of the present invention, is considered to be very promising as a liquid crystal alignment film that can be obtained by baking at a low temperature. It should be noted that, when any of the liquid crystal alignment agents of Examples 7 to 10 was used, a liquid crystal alignment film and a liquid crystal display element could be suitably obtained. [Industrial Applicability]

[0134] The liquid crystal display element produced using the liquid crystal alignment agent of the present invention can be a highly reliable liquid crystal display device, and can be suitably used as a display element of various types, such as a TN liquid crystal display element, an STN liquid crystal display element, a TFT liquid crystal display element, a VA liquid crystal display element, and an OCB liquid crystal display element.

Claims

1. The polymer is obtained from a diamino compound (a1) represented by the following formula (3-1), a diisocyanate (a2), and a monomer (a3) ​​having a specific side chain and selected from diamines and diisocyanates, the monomer (a3) ​​being represented by the following formula (2), except that the monomer (a3) ​​overlaps with the diamino compound (a1) and the diisocyanate (a2). 【Chemistry 1】 In formula (3-1), R 1 represents an alkyl group having 1 to 4 carbon atoms, which may be branched. B represents a single bond or an aliphatic hydrocarbon group having 1 to 5 carbon atoms. Ra and Rb each independently represent a hydrogen atom or an aliphatic hydrocarbon group having 1 to 2 carbon atoms. 【Chemistry 2】 In formula (2), N represents an amino group or an isocyanate group, R 3 represents a single bond, -O-, -NHCO-, -CONH-, -COO-, or -CH 2 O-, X 1 , X 2 , and X 3 each independently represents a benzene ring or a cyclohexane ring; p, q, and r each independently represent an integer of 0 or 1; R 4 represents a hydrogen atom, an alkyl group having 1 to 22 carbon atoms, or a monovalent organic group having a steroid skeleton and 17 to 25 carbon atoms. 3 is a single bond, p=q=r=0, and R 4 Excluding those where is a hydrogen atom.

2. The polymer according to claim 1, wherein the diisocyanate (a2) is at least one of structures represented by the following formulas (4-1) to (4-13). 【Chemistry 3】 In the formula, R 5 and R 6 each independently represents an aliphatic hydrocarbon group having 1 to 10 carbon atoms.

3. A liquid crystal aligning agent comprising the polymer according to claim 1 or 2.

4. A liquid crystal alignment film obtained from the liquid crystal aligning agent according to claim 3.

5. A liquid crystal display device using the liquid crystal alignment film according to claim 4.

Citation Information

Patent Citations

  • JP1970022159B

  • JP1971009572Y1

  • JP1974012080A

  • JP1975012085A

  • Liquid crystal sandwiching substrate

    JP1980002235A